Canine peripheral non-conventional TCRαβ+ CD4-CD8α- double-negative T cells show T helper 2-like and regulatory properties - Protschka, Martina; Di Placido, Daniela; Moore, Peter F.; Büttner, Mathias; Alber, Gottfried; Eschke, Maria (Frontiers in Immunology, 2024)
The dog is an important companion animal and also serves as model species for human diseases. Given the central role of T cells in immune responses, a basic understanding of canine conventional T cell receptor (TCR)αβ+ T cells, comprising CD4+ single-positive (sp) T helper (Th) and CD8α+ sp cytotoxic T cell subsets, is available. However, characterization of canine non-conventional TCRαβ+ CD4+ CD8α+ double-positive (dp) and TCRαβ+ CD4-CD8α-double-negative (dn) T cells is limited. In this study, we performed a comprehensive analysis of canine dp and dn T cells in comparison with their conventional counterparts. TCRαβ+ T cells from peripheral blood of healthy dogs were sorted according to their CD4/CD8α phenotype into four populations (i.e. CD4+ sp, CD8α+ sp, dp, and dn) and selected surface markers, transcription factors and effector molecules were analyzed ex vivo and after in vitro stimulation by RT-qPCR. Novel characteristics of canine dp T cells were identified, expanding the previously characterized Th1like phenotype to Th17-like and Th2-like properties. Overall, mRNA expression of various Th cellassociated cytokines (i.e. IFNG, IL17A, IL4, IL13) in dp T cells upon stimulation highlights their versatile immunological potential. Furthermore, we demonstrated that the CD4-CD8α-dn phenotype is stable during in vitro stimulation. Strikingly, dn T cells were found to express highest mRNA levels of type 2 effector cytokines (IL4, IL5, and IL13) upon stimulation. Their strong ability to produce IL-4 was confirmed at the protein level. Upon stimulation, the percentage of IL-4-producing cells was even higher in the non-conventional dn than in the conventional CD4+ sp population. Constitutive transcription of IL1RL1 (encoding IL-33Rα) further supports Th2-like properties within the dn T cell population. These data point to a role of dn T cells in type 2 immunity. In addition, the high potential of dn T cells to transcribe the gene encoding the co-inhibitory receptor CTLA-4 and to produce the inhibitory cytokine IL-10 indicates putative immunosuppressive capacity of this population. In summary, this study reveals important novel aspects of canine non-conventional T cells providing the basis for further studies on their effector and/or regulatory functions to elucidate their role in health and disease.